Overcoming dyscalculia and difficulties with number - Bird, Ronit (Thousand Oaks : SAGE Publications, 2021)
'In writing this practical book, Ronit Bird has drawn on her teaching and training experience to create teaching plans for key numeracy topics, aimed at those working with students aged 9-16. She provides detailed strategies for teaching numeracy skills through a progression of practical activities and visualisation techniques which build the self-esteem of students who need extra help and give them a basic foundation in number. While the plans cover the National Numeracy Strategy, they can also be used in any setting where maths is being taught. Topics covered include: - games and puzzles for learning number components - bridging - multiplication - division - reasoning strategies A bank of accompanying resources, games, activities and Su-Doku puzzles is available on the companion website for the book. This is an ideal resource for both class teachers and maths subject teachers, and is equally useful for teaching assistants and learning support assistants'--
Includes index.
Keywords: Acalculia in children; Acalculia -- Patients -- Education; Mathematics -- Study and teaching -- Activity programs; Special education -- Mathematics; Special education -- Activity programs